Gender-based vulnerabilities for women during natural disasters in Bangladesh - Fatema, Syadani Riyad; East, Leah; Islam, Shahidul; Usher, Kim (Frontiers in Communication, 2023)
Factors that negatively impact women’s disaster experiences include poor disaster preparedness, lack of access to a safe place, displacement worries, distance from shelters, risk of abuse in shelters, poverty, and low cultural position of women in rural Bangladesh. This study aimed to give voice to women who experienced gender-based vulnerabilities during natural disasters. The research was conducted with women in the two disaster-prone areas utilising a qualitative approach. Women, aged 18 years or above, who were permanent residents of the selected disaster-prone areas and have experienced one or more disasters, were invited to participate in the study. Twenty-four women volunteered to participate. Data were collected through semi-structured in-depth interview recordings containing questions on sociodemographic characteristics and open-ended questions to assess gender-based vulnerabilities during disasters; data were analysed using thematic analysis techniques. One main theme and six sub-themes emerged from the analysis. Women were often in the middle of making life choices between the risk of being abused and death in disasters. Shelters lacked privacy, heightened the risk of abuse, and women faced social stigma if displaced from their homes during a disaster. The women also experienced health risks because of inadequate hygiene and poor living arrangements such as a lack of adequate shelters, toilet facilities, and secure gender-segregated living arrangements if relocation was essential during a disaster. Findings from this study provide guidance to policymakers and disaster aid organizations on disaster preparedness and post-disaster facilities to address the socio-cultural needs of rural women in disaster-prone areas of Bangladesh.